2006
DOI: 10.1074/jbc.m606310200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by Which Bloom Protein Can Disrupt Recombination Intermediates of Okazaki Fragment Maturation

Abstract: Bloom syndrome is a familial genetic disorder associated with sunlight sensitivity and a high predisposition to cancers. The mutated gene, Bloom protein (BLM), encodes a DNA helicase that functions in genome maintenance via roles in recombination repair and resolution of recombination structures. We designed substrates representing illegitimate recombination intermediates formed when a displaced DNA flap generated during maturation of Okazaki fragments escapes cleavage by flap endonuclease-1 and anneals to a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Instead, we found that RPA could promote strand annealing and subsequent recombination (34). Our current results show that RPA-coated flaps of a variety of lengths could be precursors to recombination, suggesting a need for Dna2 helicase to eliminate these flaps before recombination occurs.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Instead, we found that RPA could promote strand annealing and subsequent recombination (34). Our current results show that RPA-coated flaps of a variety of lengths could be precursors to recombination, suggesting a need for Dna2 helicase to eliminate these flaps before recombination occurs.…”
Section: Discussionmentioning
confidence: 52%
“…It has been hypothesized that some flaps become long enough to be coated by RPA (30,32,33). When we tested flap substrates with RPA-coated flaps, we were surprised to find that the RPA promoted annealing of the flap to other single-stranded template DNA (34). This result suggested that RPA alone can support rather than suppress recombination.…”
Section: Replication Protein a (Rpa)mentioning
confidence: 75%
See 2 more Smart Citations
“…In vitro studies with use of substrates similar to Okazaki fragments showed BLM stimulation of flap endonuclease [105] (a protein that functions in lagging strand synthesis [106]). BLM functions to prevent the association of homologous sequences in the displaced flap DNA of the Okazaki fragment and the sister chromatid [107][108][109][110]. D-loops are formed when a ssDNA tail invades a homologous duplex, and BLM has a preference for dissociating D-loops with a 5' invaded end suggesting a selection of recombination intermediates that are not extended by polymerase [93,111,112].…”
Section: Blm and Recql4mentioning
confidence: 99%